Carotid Baroreceptor Stimulation for the Treatment of Resistant Hypertension - Vasilios Papademetriou; Michael Doumas; Charles Faselis; Constantinos Tsioufis; Stella Douma; Eugene Gkaliagkousi; Chrysanthos Zamboulis (International Journal of Hypertension)
Interventional activation of the carotid baroreflex has been an appealing idea for the management of resistant hypertension for several decades, yet its clinical application remained elusive and a goal for the future. It is only recently that the profound understanding of the complex anatomy and pathophysiology of the circuit, combined with the accumulation of relevant experimental and clinical data both in animals and in humans, has allowed the development of a more effective and well-promising approach. Indeed, current data support a sustained over a transient reduction of blood pressure through the resetting of baroreceptors, and technical deficits have been minimized with a subsequent recession of adverse events. In addition, clinical outcomes from the application of a new implantable device (Rheos) that induces carotid baroreceptor stimulation point towards a safe and effective blood pressure reduction, but longer experience is needed before its integration in the everyday clinical practice. While accumulating evidence indicates that carotid baroreceptor stimulation exerts its benefits beyond blood pressure reduction, further research is necessary to assess the spectrum of beneficial effects and evaluate potential hazards, before the extraction of secure conclusions.